Sosialisasi Optimalisasi Kinerja Pemerintahan Kelurahan dalam Meningkatkan Partisipasi Masyarakat pada Program Pembangunan di Kelurahan Sungai Jingah: Pengabdian - Devia Hetty Hernany; Fakhsiannor; Amelia Puspita; Budi Setiawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service aims to increase community participation in development programs implemented by the Sungai Jingah Village government. This activity is carried out through socialization which aims to optimize the performance of the village government in implementing development programs by involving active community participation. Increasing community participation is very important in creating sustainable development and in accordance with community needs. The program implemented involves various stakeholders, such as village officials, community leaders, and local residents. Through an educational approach, it is hoped that the community can understand the importance of their role in village development and contribute to decision making. The results of this activity show an increase in community understanding of their role in development and increased participation in development programs in Sungai Jingah Village.